Bridging images and natural language with deep learning - Gu, Jiuxiang (2019)
Throughout the thesis, I demonstrate how each of the proposed methods can bridge the gap between images and natural language. Experimental results on public vision and language datasets have shown all these methods are able to obtain significant performance improvement on vision and language tasks such as image captioning and cross-modal retrieval.